Studi Kajian Alasan Masyarakat Memilih Bolu Meranti Sebagai Oleh-Oleh Medan - Humairah, Alifah; Br Barus, Novita Putri Ramadhani; Jannah, Ayu Roudhatul; Satria, Wisnu; Rangkuty, Dewi Mahrani (CiDEA Journal, 2022)
Meranti sponge cake culinary, started by an ordinary housewife who has a hobby of making cakes so that it is liked by family and even neighbours, eventually became a small business flooded with orders from neighbours. Bolu gulung Meranti is growing rapidly and has even become one of the typical souvenirs of Medan. Product attractiveness is everything that traders/sellers can offer to be noticed, requested, sought after, purchased, consumed by the market as a fulfilment of market needs or desires. The purpose of this study is to examine the background of the existence of Meranti sponge cake culinary, to find out how much Meranti sponge cake is enjoyed, to find out how Meranti sponge cake marketing techniques. This is a qualitative descriptive study with a literature study research method through decision studies sourced from journals of previous research results. The results of the review study show that Meranti's enthusiasts are greatly increasing by around 5% - 10% per year. The marketing techniques carried out by Meranti are improving product quality by innovating, increasing or expanding branches/shopping access (shopeefood, grabfood), making interesting new products so that consumers are interested in trying, increasing the potential of employees to help smooth the selling of Meranti sponge cake.